If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 12 = 75 Reorder the terms: 12 + 7y = 75 Solving 12 + 7y = 75 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 7y = 75 + -12 Combine like terms: 12 + -12 = 0 0 + 7y = 75 + -12 7y = 75 + -12 Combine like terms: 75 + -12 = 63 7y = 63 Divide each side by '7'. y = 9 Simplifying y = 9
| .99d=10+.89 | | A-32=18 | | 14d+4d-16d=10 | | z+3.27=8.36 | | -5n+2=33 | | 4(-2w+1)+3=8(-1w-5)+47 | | 6c=2 | | 6h/2 | | 5x+418=7 | | 4w+3w-3w-2w-w=14 | | -10x+2=-38 | | 2x^2+10x-6x-30=4+8x+x^2 | | -180=1800-(-360) | | 6(x-5)=7[x-(3-x)] | | 13k-9k=4 | | 4/5y-8=2/5y-2 | | 9s-3s+s+2s-5s=8 | | 10r=2r+10 | | 2/3x-1/15=2/5 | | 0.5x+5=6 | | x-1+x+10=180 | | 6m+13=4m+3 | | 2k+k+45= | | X-7/4=2 | | X(3X+9)=264 | | -6(x+6)-5=2(x+7) | | 12w-8w-3w=12 | | 4g=144 | | -14w+7-20+12w= | | -42-7y=-105 | | -8y+11=83 | | U-6=-8 |